SISTEM INFORMASI PENJUALAN OBAT BERBASIS WEB DENGAN IMPLEMENTASI ALGORITMA SEQUENTIAL SEARCH PADA APOTEK BUNDA - Yuliana Ecik Manang; Kristina Sara; Finansius Mando (Jurnal Riset Teknik Komputer, 2025)
Currently, the process of recording drug sales and drug purchase transactions at Bunda Pharmacy is still done manually, namely using a ledger (manual). So this is very ineffective and inefficient and can cause errors when inputting data, recording drug data, drug stock, sales and purchases or when searching for drug data. Therefore, this was done to design a web information system using qualitative methods using the waterfall method and using a sequential search algorithm to search for drug names, categories, expiration dates, selling prices, purchase prices or drug units and sequential search algorithms to sort data from drug data or expiration dates. With the information system that has been designed, it will make it easier for pharmacy officers (Pharmacists) to collect, as well as look for information on drug data when inputting transaction data and will make it easier to check drugs that need to be restocked so that there are no errors in the sales process. The system design in this research uses DFD, ERD and Table Relations, The system design in this research uses DFD, ERD and Table Relations.